Evaluation of anti - inflammatory and anti –biofilm activity ofSilver nanoparticle using wattakakavolubilislinn. F. - WASEEM IQBAL KHANDAY,; MADHANRAJ RAJENDRAN,; EYINI MUTHUKUMARASAMY,; BALAJI PAULRAJ, (International Journal of Pharma and Bio Sciences, 2017)
Silver nanoparticles (AgNPs) are an important class of nanomaterial for a wide range of biomedical applications. Synthesis of AgNPs through biological route is preferred due to its eco-friendly and economic aspects. Green synthesis provides advancement over chemical and physical method.Persistent infections caused by bacterial biofilms have been associated with a number of medical conditions including periodontal disease, endocarditis, osteomyelitis and cystic fibrosis. Preventing biofilm formation would be a more logical option than treating it. The main strategy to prevent biofilm formation is to clean and disinfect regularly before bacteria attach firmly to surfaces. Anti-inflammatory activity was calculated by the percentage of HRBC membrane stabilization or protection and the biofilm formation was determined by the congo red agar method and tissue culture plate method. The present study explored the Wattakaka volubilis which are efficient producers of AgNPs and could act as safe and cost-effective with potential biological applications.